Effect of Different Levels of Direct-fed Microbials Plus Exogenous Fibrolytic Enzymes Additives on the Growth Traits of Dairy Calves - Elifnur Hirik İlhan; Mete Yanar (Journal of Agricultural Sciences)
The study was carried out to investigate to determine effects of the different levels of the direct-fed microbials (DFM) plus exogenous feed enzymes (EFE) on the body weights, weight gains, feed efficiency ratio, some behavioral traits as well as fecal consistency index of male Brown Swiss calves. For this purpose, 18 male Brown Swiss calves were allocated to three groups (control, 10 g and 20 g head/day of DFM plus EFE). Weights obtained at weaning time and 6 months of age of the calves in 10 g head/day of DFM plus EFE group were respectively 7.3% and 7.1% heavier than these of animals in control group. The calves in 10 g head/day of DFM plus EFE group in pre-weaning and between birth and 6 months of age periods also had respectively 16.0% and 7.3% higher total weight gains than calves in the control group. Feed efficiency ratio of the calves fed diets with 10 g DFM plus EFE had 64.2% better than that of calves in control group. Average fecal consistency score of the calves fed a diet supplemented with 10 g head/day of DFM plus EFE had the lowest score (P<0.05) (i.e., less scouring) compared to other treatment groups in pre-weaning period as well as between birth and 6 months of age. Furthermore, behavioral activities of the calves were not significantly influenced by DFM plus EFE additives except for the percentage of time spent for lying. The study revealed that the feeding of DFM plus EFE to male Brown Swiss calves until 6 months of age had positive but not statistically significant improvement on the growth traits and feed efficiency ratio. On the other hand, it was concluded that the level of 10 g head/day of the DFM plus EFE additives could be beneficial for reducing incidence of diarrhea in the dairy calves.